Magnetic Resonance Imaging of Transplanted Neural Stem Cells in Parkinson Disease Rats - 杨林 夏鹰 赵洪洋 赵甲山 朱贤立 (Journal of Huazhong University of Science and Technology. Medical sciences, 2006)
Summary： In this study we implanted magnetically labeled neural stem cells （NSCs） in PD rats and then monitored their survival and migration in the host brain by magnetic resonance imaging （MRI）. The mesencephalic NSCs were obtained from the brain of SD rats. Superparamagnetic iron oxide （SPIO） was transferred to NSCs by Lipofectamine transfection. Eighteen PD lesioned rats were selected for transplantation by evaluation of their rotational behavior in response to amphetamine and randomly assigned to 3 groups, i.e., sham group, PBS group and NSCs transplanted group, with 6 rats in each group. MR scanning was performed at 1, 2, 4, 6, 8 and 10 week（s） following transplantation. At the meantime, rotational behavior was assessed in each group. Our results showed that SPIO particles were clearly visible with Prissian blue staining in neurospheres and cells derived from NSCs. The rotational behavior of the NSCs transplanted group was remarkably improved compared with that of sham group and PBS group （P〈0.05）. In vivo MR tracking of NSCs showed that SPIO labeling led to a strong susceptibility change of signal 1 week after transplantation on T2 weighted images. And a large circular hypointense signal appeared in the transplanted area on T2＊ gradient echo images Ten weeks following transplantation, the hypointense signal on T2 weighted and T2＊ gradient echo images was still displayed. It is concluded that SPIO particles could label NSCs effectively, and MRI detection of SPIO labeled cells is a promising method and novel approach to analyzing the NSCs following transplantation in the treatment of PD.